A method for the quantitative determination of glycerophospholipid regioisomers by UPLC-ESI-MS/MS - SARIYAR AKBULUT, BERNA (SPRINGER HEIDELBERG, 2019)
Diacyl glycerophospholipids (GPs) belong to the most abundant lipid species in living organisms and consist of a glycerol backbone with fatty acyl groups in sn-1 and sn-2 and a polar head group in the sn-3 position. Regioisomeric mixed diacyl GPs have the same fatty acyl composition but differ in their allocation to sn-1 or sn-2 of the glycerol unit. In-depth analysis of regioisomeric mixed diacyl GP species composed of fatty acyl moieties that are similar in length and degree of saturation typically requires either chemical derivatization or sophisticated analytical instrumentation, since these types of regioisomers are not well resolved under standard ultra-performance liquid chromatography (UPLC) conditions. Here, we introduce a simple and fast method for diacyl GP regioisomer analysis employing UPLC tandem mass spectrometry (MS/MS). This GP regioisomer analysis is based both on minor chromatographic retention time shifts and on major differences in relative abundances of the two fatty acyl anion fragments observed in MS/MS. To monitor these differences with optimal precision, MS/MS spectra are recorded continuously over the UPLC elution profile of the lipid species of interest. Quantification of relative abundances of the regioisomers was performed by algorithms that we have developed for this purpose. The method was applied to commercially available mixed diacyl GP standards and to total lipid extracts of Escherichia coli (E. coli) and bovine liver. To validate our results, we determined regioisomeric ratios of phosphatidylcholine (PC) standards using phospholipase A(2)-specific release of fatty acids from the sn-2 position of the glycerol backbone. Our results show that most analyzed mixed diacyl GPs of biological origin exhibit significantly higher regioisomeric purity than synthetic lipid standards. In summary, this method can be implemented in routine LC-MS/MS-based lipidomics workflows without the necessity for additional chemical additives, derivatizations, or instrumentation.
Keywords: Lipidomics; Glycerophospholipids; Position isomerism; Regioisomers; UPLC-MS; MS; Targeted MS; MS; COLLISION-INDUCED DISSOCIATION; OZONE-INDUCED DISSOCIATION; MASS-SPECTROMETRY; DOUBLE-BOND; LIQUID-CHROMATOGRAPHY; PHOSPHOLIPASE A(2); PHOSPHATIDYLCHOLINES; SEPARATION; POSITIONS; LIPIDS